1987
DOI: 10.1111/j.1348-0421.1987.tb03122.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Groups of Mycobacterium avium Complex Strains Determined According to the Susceptibility to Rifampicin and Ansamycin

Abstract: Mycobacterium avium complex strains previously not exposed to any antituberculosis agents could be divided into two groups according to their susceptibility to rifampicin and ansamycin; one group susceptible to 80 ,ugiml rifampicin and to 1.25 ,ugiml ansamycin, and another resistant to these concentrations. In each group, the ratio of the minimal inhibitory concentration of ansamycin against that of rifampicin was greatly different depending on the strain. This naturally occurring resistance to rifampicin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Successively, several authors (5-7) reported that the SmT colonial morphology correlated with resistances to rifampicin, streptomycin, kanamycin, and viomycin, and the SmD colonial morphology with susceptibilities to these drugs. Tsukamura (14,15) observed that the M. avium complex strains are divided into two groups, one resistant to most antituberculosis drugs and another susceptible to these, and that such resistances or susceptibilities well correlated with clinical effect of chemotherapy. Moreover, it was observed that the resistances or susceptibilities to rifampicin, minocycline, streptomycin, kanamycin, enviomycin, and kitasamycin in M. avium complex strains isolated from patients previously not treated by any antituberculosis drugs do not appear at random but do appear showing correlations to each other (16).…”
mentioning
confidence: 99%
“…Successively, several authors (5-7) reported that the SmT colonial morphology correlated with resistances to rifampicin, streptomycin, kanamycin, and viomycin, and the SmD colonial morphology with susceptibilities to these drugs. Tsukamura (14,15) observed that the M. avium complex strains are divided into two groups, one resistant to most antituberculosis drugs and another susceptible to these, and that such resistances or susceptibilities well correlated with clinical effect of chemotherapy. Moreover, it was observed that the resistances or susceptibilities to rifampicin, minocycline, streptomycin, kanamycin, enviomycin, and kitasamycin in M. avium complex strains isolated from patients previously not treated by any antituberculosis drugs do not appear at random but do appear showing correlations to each other (16).…”
mentioning
confidence: 99%